2016
DOI: 10.1021/acscatal.6b02331
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Active Sites in Supported Ni Catalysts during Butene Oligomerization by Operando Spectroscopy under Pressure

Abstract: Supported Ni catalysts have been studied during the dimerization of butenes by operando electron paramagnetic resonance (EPR) and in situ X-ray absorption spectroscopy (XAS) at 353 K and up to 16 bar. Single Ni I /Ni II shuttles were identified as active sites, whereby the conversion of initial Ni I to Ni II by oxidative addition of butene is obviously faster than the re-reduction of Ni II to Ni I by reductive elimination of the C8 product, rendering the equilibrium percentage of Ni I small. At p ≤ 2 bar, Ni I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 20 publications
1
32
0
Order By: Relevance
“…the most selective catalysts in the ODH of ethane). For comparison, the XAS spectrum corresponding to metallic Ni is also included in this figure . A decrease in the "white line" intensity is observed for both 20NiO/TiO2 and 92Ni-Nb-O samples, with respect to unselective NiO catalyst, likely due to a decrease in the average oxidation state of Ni atoms in modified catalysts [49]. More interestingly, it can be observed that the drop of the intensity is more drastic for promoted 92Ni-Nb-O than in the case of supported 20NiO/TiO2.…”
Section: Figurementioning
confidence: 81%
“…the most selective catalysts in the ODH of ethane). For comparison, the XAS spectrum corresponding to metallic Ni is also included in this figure . A decrease in the "white line" intensity is observed for both 20NiO/TiO2 and 92Ni-Nb-O samples, with respect to unselective NiO catalyst, likely due to a decrease in the average oxidation state of Ni atoms in modified catalysts [49]. More interestingly, it can be observed that the drop of the intensity is more drastic for promoted 92Ni-Nb-O than in the case of supported 20NiO/TiO2.…”
Section: Figurementioning
confidence: 81%
“…This is accompanied by stabilization of tri-and tetravalent nickel oxide species by aluminum [21], which in the presence of olefins (in the present case primarily 2-butene) are reduced to catalytically active nickel hydride species [22]. In addition, using in situ electron paramagnetic resonance (EPR) spectroscopy correlated with XANES/EXAFS, the formation of a Ni I /Ni II redox pair was detected during the dimerization of n-butenes, which are present as single sites [23,24]. For the formation of this species, a reaction cycle has been proposed, which requires the interaction of olefins with Ni II in the direct vicinity of a Brønsted acid site.…”
Section: Introductionmentioning
confidence: 84%
“…The main products of this step are butenes. This mechanism proceeds via the oxidative coupling of ethene [53,54]. However, ethene could be further oligomerized to hexene.…”
Section: Modified Network Including Cracking (Network Ii)mentioning
confidence: 99%